History of Jewish philosophy - Frank, Daniel H., 1950-; Leaman, Oliver, 1950- (Routledge history of world philosophies, 1997)
Jewish philosophy is often presented as an addendum to Jewish religion rather than as a rich and varied tradition in its own right, but the History of Jewish Philosophy explores the entire scope and variety of Jewish philosophy from philosophical interpretations of the Bible right up to contemporary Jewish feminist and postmodernist thought. The links between Jewish philosophy and its wider cultural context are stressed, building up a comprehensive and historically sensitive view of Jewish philosophy and its place in the development of philosophy as a whole. Includes:· Det.